Estrategias para mejorar la calidad de atención farmaceútica en el establecimiento privado farmacia Funegra enero 2015 –enero 2016” - De La Puente Orellano, Anggelha Marytte (2016)
This report describes practices Pre-Professional activities in the field of private pharmacy that is part of the requirements for obtaining the professional title of pharmaceutics. The development of pre-professional practice was conducted between January 8, 2015 to January 8, 2016 at the Pharmacy Funegra, a company dedicated to health, with a deep commitment to service and clear orientation towards the needs of people, under the guidance of the Pharmaceutical Chemist Funegra Francisco Llanos. the company where the Pre-Professional Practice and the various tasks performed during the probationary period, both technical and administrative, in general, are focused on the efficient management of a pharmaceutical office, safe dispensing of medicines was carried out described, care and pharmaceutical guidance to patients, custody substance under legal control, induction and staff training, enrollment rates at the observatory, mentioning the objectives of each and how they were carried out on the premises, indicating briefly what the Chemist Pharmacist role in such activities and the work performed by the employee staff within them. All important to the operation of the premises, some of these being governed by laws and government regulations in our country. In addition, an analysis was performed to improve pharmaceutical care and thus provide quality care to the public, improving their quality of life.